Perbandingan Kepatuhan Terhadap Prinsip Syariah dalam Pembiayaan Bank Syariah - Qalbia, Farah; Santoso, Seger; Ruslaini (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2024)
This study examines the compliance of Islamic banks with Shariah principles, specifically riba, gharar, and maysir, in financing practices through a literature review. Analysis of eight previous studies explores the effectiveness of implementation and the challenges encountered. The findings indicate that despite significant efforts through Shariah-compliant product designs such as murabahah and istisna', challenges persist, particularly in resembling conventional interest practices, contract complexity, and speculative risks. Factors such as the role of Shariah supervisory boards, regulations, and consumer awareness are pivotal in improving compliance. This study highlights the importance of continuous innovation and rigorous oversight to achieve better adherence to Shariah principles. However, this research is limited by the lack of empirical data and specific geographic coverage, opening avenues for further studies.